Automated shear-wave splitting analysis for single- and multi-layer anisotropic media - Hudson, T; Asplet, J; Walker, A (Seismica, 2023)
Shear-wave velocity anisotropy is present throughout the earth. The strength and orientation of anisotropy can be observed by shear-wave splitting (birefringence) accumulated between earthquake sources and receivers. Seismic deployments are getting ever larger, increasing the number of earthquakes detected and the number of source-receiver pairs. Here, we present a new Python software package, SWSPy, that fully automates shear-wave splitting analysis, useful for large datasets. The software is written in Python, so it can be easily integrated into existing workflows. Furthermore, seismic anisotropy studies typically make a single-layer approximation, but in this work we describe a new method for measuring anisotropy for multi-layered media, which is also implemented. We demonstrate the performance of SWSPy for a range of geological settings, from glaciers to Earth's mantle. We show how the package facilitates interpretation of an extensive dataset at a volcano, and how the new multi-layer method performs on synthetic and real-world data. The automated nature of SWSPy and the discrimination of multi-layer anisotropy will improve the quantification of seismic anisotropy, especially for tomographic applications. The method is also relevant for removing anisotropic effects, important for applications including full-waveform inversion and moment magnitude analysis.